2003
DOI: 10.1001/jama.289.5.553
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcysteine for Prevention of Acute Deterioration of Renal Function Following Elective Coronary Angiography and Intervention

Abstract: ONTRAST NEPHROPATHY IS A recognized complication after coronary angiography and intervention that has been associated with prolonged hospitalization and adverse clinical outcomes. 1-3 It is reported that 14.5% of patients develop a 25% increase in serum creatinine levels following cardiac catheterization. 2 This problem assumes greater and greater importance with increased use of invasive radiological procedures to diagnose and treat coronary artery disease. Contrast nephropathy is potentially preventable beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
8

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(73 citation statements)
references
References 35 publications
2
62
1
8
Order By: Relevance
“…It is interesting that acetylcysteine does seem to have a protective role in women beyond hydration although we do not have large numbers of women to show this conclusively. Our finding contradicts recent studies that showed a protective effect of N-acetylcysteine [1][2][3][4][5][6] in selected patients with stable RI; other recent investigations failed to find any such beneficial effects. [7][8][9][10][11] These studies only examined patients with chronic, stable RI undergoing elective procedures.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is interesting that acetylcysteine does seem to have a protective role in women beyond hydration although we do not have large numbers of women to show this conclusively. Our finding contradicts recent studies that showed a protective effect of N-acetylcysteine [1][2][3][4][5][6] in selected patients with stable RI; other recent investigations failed to find any such beneficial effects. [7][8][9][10][11] These studies only examined patients with chronic, stable RI undergoing elective procedures.…”
Section: Discussioncontrasting
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] However, these trials studied patients with chronic stable RI undergoing elective procedures. Accordingly we sought to evaluate the effectiveness of N-acetylcysteine and hydration in unselected patients with both acute and stable RI undergoing urgent or elective cardiac or peripheral angiography.…”
Section: Introductionmentioning
confidence: 99%
“…46 In a cohort of 224 patients with chronic renal insufficiency (creatinine > 1.5 mg/dl or creatinine clearance < 60 ml/min), CIN occurred in 11% of patients in the standard dose group and in 3.5% in the high dose group (p = 0.04). In the subgroup with the contrast dose ≥ 140 ml, CIN was more frequent in the standard group (18.9%) than in the high dose group (5.4%, p = 0.04), whereas no difference was found in the low-dose (< 140 ml) subgroup.…”
Section: N-acetylcysteinementioning
confidence: 99%
“…Patients with chronic renal insufficiency receiving large contrast dose (> 140 ml) may also be given high-dose NAC (2 X 1200 mg). 5,46 …”
Section: Management Of Cin and Therapeutic Recommendationmentioning
confidence: 99%
“…We identified trials by performing a MEDLINE search as well as by reviewing the references of the identified articles. [9][10][11][12][13] Trials were included if they were published in the English language and met the following criteria: design as prospective, randomized, controlled trials; inclusion of patients who were at high risk due to their renal status (impaired renal function); use of low-osmolality nonionic contrast media intra-arterially for diagnostic or therapeutic cardiovascular procedures; use of N-acetylcysteine to prevent contrast nephropathy in addition to intravenous saline hydration; administration of a total of four doses of N-acetylcysteine starting the day before procedure and continued through the day of procedure. All of the trials compared orally administered N-acetylcysteine and peri-procedural hydration (treatment group) to peri-procedural hydration alone (control group).…”
Section: Trial Selectionmentioning
confidence: 99%